The Ithnab Style in Quranic Stylistics: A Study of Structure - Anggraini, Dwi Puspa; Syihabuddin, Syihabuddin; Sopian, Asep (Fakultas Keguruan dan Ilmu Pendidikan,Universitas Jambi, 2023)
This research explores the use of the ithnab style in the stylistic analysis of the Quran, focusing on sentence structure. Stylistic analysis methods are employed to identify and analyze the repetition of words or phrases in the Quranic text. The main objective of this study is to uncover how the ithnab style is used to reinforce meaning and messages in this sacred text. The results of the analysis indicate that the ithnab style is employed in various forms in the Quran, including the repetition of words, phrases, or concepts. This repetition aims to provide strong emphasis on the message or meaning being conveyed. Through structured repetition, Quranic verses are able to deepen understanding and evoke emotional effects on readers or listeners. Overall, this research provides insights into the significance of the ithnab style in shaping the structure and meaning of the Quran. The implications of this study go beyond language analysis and also impact spiritual and aesthetic understanding in Islam. The use of the ithnab style helps unearth deeper meanings of divine messages in the Quran.